Quality of life and its determinants among older people living in the rural community in Sri Lanka - Rathnayake, Sarath; Siop, Sidiah (Jaipur, 2015)
In recent decades, the proportion of people aged 60 years and above has increased rapidly in Sri Lanka. With this unprecedented increase, Sri Lanka faces great challenges in meeting the health and social need of the older people. There is a paucity of information related to quality of life (QOL)and related factors among elderly in Sri Lanka. Therefore, this study planned to examine quality of life and its determinants among older people living in a rural community in Sri Lanka. This community based cross-sectional survey was conducted among a random sample of 336 old people aged 60 years and above living in the community. Respondents were interviewed individually using a structured interview questionnaire. QOL was measured by the Older People QOL questionnaire (OPQOL). Univariate and multivariate logistic regression analysis were used to determine the factors influencing QOL. The most agreed/strongly agreed response in OPQOL items was "religious, belief or faith is important to my QOL" (96.5%) and the most disagreed/strongly disagreed response was "I do not have enough money to pay for household repairs or help needed in the house" (85.4%). The standardized QOL score based on OPQOL was 63.86. The highest and the lowest standardized domain scores were reported by the domains of 'home and neighborhood' (71.4) and 'financial circumstances' (51.8), respectively. Determinants of poor QOL among older people were living alone, poor family income, presence of chronic kidney diseases and poor self-rated health. This study provides baseline data on QOL among older people in the rural community in Sri Lanka. It is concluded that older people experience a moderate level of QOL and religion is an important aspect of QOL. Health and social workers can use this findings to plan appropriate interventions to improve QOL in community dwelling older people.